Relationship of Adaptation and Homesickness in Rantau Students in Faculty of Psychology of Muhammadiyah Purwokerto University (Sains Humanika, 2021)
Today, many students use the term homesick to describe their situation when they miss their family, are sick, or feel uncomfortable with the situation in their new environment. One emergence of homesickness is a poor adaptation of the student in the new environment. A good adaptation will help the individual create a sense of comfort and happiness in his new environment. This study aims to examine the relationship between adaptation and homesickness in rantau students. The subjects in this study selected by the criteria were rantau students from Faculty of Psychology, Universitas Muhammadiyah Purwokerto, living in boarding houses around campus and not having relatives in Purwokerto with total 35 respondents. This research used quantitative method and for collecting the data using adaptations scales of Archer et al.'s Homesickness Questionnaire and Behavioral Adaptation owned by Umdatun Watsiqoh. The results of the correlation test of the two variables, it shows that there is no correlation between adaptation and homesickness. The correlation of adaptation and homesickness has a negative relationship or inversely related to the correlation coefficient value of -0.086, but the relationship was not proven significant because the significance value obtained (p > 0,05).
Keywords: Adaptation; Homesickness; Rantau Students.